SYSTEMATIC REVIEW AND META-ANALYSIS ON THE RELATIONSHIP BETWEEN SLEEP PATTERNS AND COGNITIVE FUNCTIONS IN BIPOLAR DISORDER PATIENTS - Dr Alya Abdallah Youssef Al Hamadi; Dr Hafsah Abdirahiim Maalim; Dr Ashtar Kariem; Dr Meera Al Shamsi; Dr Latifa Al Abdal; Dr Noora Alomaira; Dr Hussain Aljabal; Dr. Fathima Farzana; Ramla Mehak Khan; Dr Aethar Faraj; Dr Fathima Aaliya Anwar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Bipolar disorder (BD) is a significant psychiatric condition, affecting millions globally, characterized by alternating periods of mania and depression. Cognitive impairments, often associated with mood disturbances, are increasingly being linked to sleep disturbances in both BD Type I and BD Type II patients. These impairments encompass a wide range of cognitive domains, including memory, executive functioning, and attention. The intricate relationship between sleep and cognitive function in BD patients is crucial for optimizing treatment outcomes. Objective: This systematic review and meta-analysis aim to evaluate the relationship between specific sleep patterns (e.g., sleep efficiency, latency, REM/NREM stages) and cognitive performance in BD patients, with a focus on differentiating between BD Type I and II. Furthermore, the study seeks to explore how these sleep-cognitive interactions may be moderated by demographic factors and comorbid conditions. Methodology: A comprehensive search of five databases was conducted, and 25 studies meeting strict inclusion criteria were selected for analysis. The analysis included observational studies and randomized controlled trials. A meta-analysis was performed, focusing on the correlation between sleep disturbances and cognitive outcomes across different cognitive domains and BD subtypes. Results: Results showed that sleep disturbances were more severe in patients with BD Type I than those with BD Type II, and these impairments emerged as significant predictors of cognitive dysfunction. Sleep efficiency, latency, and REM sleep were also strong predictors of cognitive performance and together accounted for 35% of the variance in cognitive outcomes. Conclusion: Contrary to early findings, evidence from recent studies supports the response that sleep management should be included in treatment protocols for BD patients to improve cognitive outcomes. Second, BD subtype-specific interventions that target sleep disturbances may also alleviate cognitive impairments, and enhance the life quality of these patients.